The Protection of the Environment under the Rome Statute - Kecskés, Gábor (The ICC at 25: Lessons Learnt, 2025)
The protection of the environment has long been part of the discourse of international humanitarian law, as has so-called “ecocide” within international criminal law. However, neither of these strict and detailed regimes of international law explicitly articulate the absolute and unrestricted protection of the environment during armed conflicts. Noted only implicitly, it remains subject to the interpretation of the relevant existing norms. This article provides a comprehensive normative overview of this particular topic. This analysis focuses on binding international treaty provisions, customary international law–having emerged from State-based domestic rules and internationally accepted customs–and other relevant, chiefly non-binding documents with soft law characteristics. This article reviews the most relevant treaties, including the 1949 post-war four Geneva Convention (as the basis of international humanitarian law), the 1976 Environmental Modification Convention, Additional Protocol I and II of 1977, and the 1998 Rome Statute, among other relevant multilateral environmental agreements. Particular focus is placed on criminal and humanitarian issues as well as soft law mechanisms under the United Nations universal system. This article evaluates the meaning and interpretation of the 1998 Rome Statute, concluding that the protection of environment can be interpreted under this Statute.Keywords: ecocide, Rome Statute, causality, environmental damage, war crimes